Characterisation of reproductive tract microbiome and immune biomarkers for bovine genital campylobacteriosis in vaccinated and unvaccinated heifers - Juli, Mst Sogra Banu; Raza, Ali; Forutan, Mehrnush; Siddle, Hannah V.; Fordyce, Geoffry; Muller, Jarud; Boe-Hansen, Gry B.; Tabor, Ala E. (Frontiers in Microbiology, 2024)
Bovine genital campylobacteriosis (BGC) is a globally important venereal disease of cattle caused by Campylobacter fetus subspecies venerealis. Diagnosis of BGC is highly challenging due to the lack of accurate diagnostic tests. To characterise the biomarkers for C. fetus venerealis infection, a total of twelve cycling heifers were selected and categorised as vaccinated (n=6) with Vibrovax ® (Zoetis™) and unvaccinated (n=6). All heifers were oestrous synchronised with a double dose of prostaglandin (PGF2a) 11 days apart and when in oestrous intravaginally challenged with 2.7x10 9 CFU live C. fetus venerealis. DNA extracted from vaginal mucus samples was screened using a C. fetus qPCR and 16S rRNA was characterised using Illumina sequencing (V5-V8 region). Relative abundances of serum proteins were calculated using sequential window acquisition of all theoretical fragment ion spectra coupled to tandem mass spectrometry (SWATH-MS) for all heifers at three timepoints: pre-challenge, post-challenge and post-recovery. Campylobacter spp. appeared two days following challenge in unvaccinated compared to 14 days in vaccinated animals, consistent with the qPCR results. Increased relative abundances of Firmicutes and Campylobacterota were identified after C. fetus venerealis challenge and were associated with C. fetus venerealis in vaccinated and unvaccinated heifers. Greater relative abundance of Streptococcus spp. was observed during oestrous rather than dioestrous. In both vaccinated and unvaccinated heifers, Acinetobacter spp. increased after challenge with higher abundance of Corynebacterium spp. in the vaccinated group. A total of 130 unique proteins were identified in the serum samples, and the number of differentially abundant proteins found was higher in the vaccinated group after recovery from infection compared to pre-and post-challenge (adjusted P < 0.05 and Log2FC > 0.2). Coglutinin, clusterin, HP homologs, vitamin D binding protein and fetuin B were identified as potential biomarkers for C. fetus venerealis infection and need further study to validate their efficiency as immune biomarkers for BGC.